Closed-form least-squares technique for adaptive linear image interpolation - Yoo, H (Electronics letters, 2007)
An adaptive linear image interpolation method based on the least-squares technique is proposed. A generic adaptive interpolation framework is introduced to provide a simple closed-form formula for adaptive image interpolation. The experimental results indicate that the proposed interpolation method outperforms existing methods in terms of objective and subjective image quality.